(3PNjQI GdeYGO aj TQM GdEQTGOs - (3GdSHRhGQj, GdNQSGfj, eMeO HGbQ Hf eMeO eDef, J (B1090(3g`s ((3ejQ TQa GdOjf Ydjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3cJGH GdUdGI GdUdGI dZI gj GdOYGA(B...s
(3BNQgG (B:s
(3eHJhQ GdBNQ, hBNQ GdehLhO(B: ...(3hGYde Cfg fbd Yf GdTjN QMeg Gddg Cfg MQe Ydi GdeYJca LejY eG jMQe Ydi GdeMQe, hGdeTghQ NdGags
(3JHUQI GdYfhGf (B:s
(3PNjQI GdeYGO aj TQM GdEQTGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B48s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B157s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B542s
Keywords: (3abg GdePGgH GdCNQis